Psychological stress creates an immune suppressive environment in the lung that increases susceptibility of aged mice to Mycobacterium tuberculosis infection - Lafuse, William P.; Wu, Qian; Kumar, Naresh; Saljoughian, Noushin; Sunkum, Shrayes; Ahumada, Omar Santiagonunez; Turner, Joanne; Rajaram, Murugesan V. S. (Frontiers in Cellular and Infection Microbiology, 2022)
Age is a major risk factor for chronic infections, including tuberculosis (TB). Elderly TB patients also suffer from elevated levels of psychological stress. It is not clear how psychological stress impacts immune response to Mycobacterium tuberculosis (M.tb). In this study, we used social disruption stress (SDR) to investigate effects of psychological stress in young and old mice. Unexpectedly, we found that SDR suppresses lung inflammation in old mice as evidenced by lower pro-inflammatory cytokine levels in bronchial lavage fluid and decreased cytokine mRNA expression by alveolar macrophages. To investigate effects of stress on M.tb infection, mice were subjected to SDR and then infected with M.tb. As previously reported, old mice were better at controlling infection at 30 days than young mice. This control was transient as CFUs at 60 days were higher in old control mice compared to young mice. Consistently, SDR significantly increased M.tb growth at 60 days in old mice compared to young mice. In addition, SDR in old mice resulted in accumulation of IL-10 mRNA and decreased IFN-γ mRNA at 60 days. Also, confocal microscopy of lung sections from old SDR mice showed increased number of CD4 T cells which express LAG3 and CD49b, markers of IL-10 secreting regulatory T cells. Further, we also demonstrated that CD4 T cells from old SDR mice express IL-10. Thus, we conclude that psychological stress in old mice prior to infection, increases differentiation of IL-10 secreting T cells, which over time results in loss of control of the infection.